PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - SUKRISPIYANTO - (STIE Indonesia Malang, 2019)
The role of humans in a company is very important, because humans are the main driver of the smooth running of the production process. Established company is to achieve the goal of obtaining optimal profit, for that the company will try as much as possible so that the goal is achieved as expected. One of the companies carried out in connection with achieving its goal is to improve employee work performance with the hope that the product achieved is increased and can master a wide market. The purpose of this study is to find out the leadership style and motivation partially influence the performance of employees at PT. Bank Mandiri (Persero) Tbk, and find out the leadership style and motivation have a simultaneous influence on the performance of PT. Bank Mandiri (Persero) Tbk employees.The population in this study were all employees of PT. Bank Mandiri (Persero) Tbk for the poor branch. The number of samples used in this study were 54 respondents using saturated sampling techniques. Method of data collection used through questionnaires, data analysis used is multiple linear regression.The results of the study prove the leadership style and motivation simultaneously have a significant influence on the performance of PT. Bank Mandiri ( Persero) Tbk employees. This means that the success of an organization is influenced by employee performance. The results of the study also prove that : the leadership style variable has a significant effect on the performance of the employees of PT. Bank Mandiri (Persero) Tbk Malang Branch, and the motivation variable significantly influences the performance of PT. Bank Mandiri (Persero) Tbk Malang Branch.Key word : leadership, motivation, performance